Zoogeography of Chiropotes albinasus (Platyrrhini, Atelidae) in southwestern Amazonia - Ferrari, S. F.; Iwanaga, S.; Coutinho, PEG; Messias, M. R.; Neto, EHC; Ramos, L. M.; Ramos, PCS (Kluwer Academic/plenum Publ, 1999)
White-nosed bearded sakis (Chiropotes albinasus) are endemic to the Madeira-Xingu interfluvium in southern Amazonia, though recent fieldwork has produced conflicting data on the southwestern limits of the species's geographic range. We reevaluated the distribution of bearded sakis on the basis of surveys from 34 sites throughout the Brazilian state of Rondonia. Chiropotes albinasus occurred at seven sites in the eastern part of the state, including two west of the Jiparana-Pimenta Bueno river system in the extreme south, but there is no record of their presence further north and west in the Jiparana-Guapore interfluvium and they were absent from the Jiparana-Mamore interfluvium. The data suggest that ecological, rather than geographic barriers restrict the distribution of Chiropotes albinasus in southern Rondonia, but are contradictory with regard to the possible determining factors. Chiropotes albinasus appears able to thrive in transitional, savanna-like ecosystems in southern Rondonia, but is unexpectedly absent from adjacent areas of terra firme forest. Syntopy with the only other pitheciine found in the state (Pithecia irrorata) appears to have a negative effect on the abundance of Chiropotes albinasus which implies that interspecific competition may reinforce a complex of limiting factors, such as the availability of key plant species. Despite showing that Chiropotes albinasus is widespread in southern Rondonia, we also confirm its absence from the western two thirds of the state, a significant reduction in the known range of the species.
Keywords: bearded sakis; Chiropotes albinasus; zoogeography; ecology; Pithecia irrorata; southwestern Amazonia